Justification of the Economic Efficiency of Reactive Power Compensation Using the Value of the Enterprise on the Example of Jsc "Bukhoroenergomarkaz" - Babanazarova N.K; Khusenov D.R; Khafizov Kh.I. (Genius Journals, 2023)
Recently, due to the large specific energy costs, it has become impossible to produce competitive products. Reducing the specific consumption of products requires the transfer of electricity to the power supply system with minimal losses. One of the ways to solve this problem is reactive power compensation with the definition of their type, rated power and installation locations.
Keywords: Reactive power; compensating device; economic efficiency